Bibliometric Analysis of CSR in Business and Management - Loso Judijanto (Westscience Press, 2026)
This study aims to map the intellectual structure and research trends of Corporate Social Responsibility (CSR) within the field of business and management using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to explore keyword co-occurrence, overlay visualization, density mapping, and collaboration networks among authors, institutions, and countries. The results reveal that CSR serves as a central research theme interconnected with sustainable development, corporate governance, stakeholder theory, ethics, and innovation. Temporal analysis indicates a shift from early governance- and ethics-oriented discussions toward more strategic and sustainability-driven perspectives, including ESG integration and business development. Collaboration networks highlight the dominant roles of scholars and institutions from developed countries, particularly the United States and the United Kingdom, while emerging economies increasingly contribute to the expansion of CSR scholarship. Overall, the findings demonstrate that CSR research has evolved into a strategic and multidisciplinary domain, emphasizing sustainability integration and global collaboration in addressing contemporary business challenges.